Resistance of rice to stem bug - Ferreira, Evane; da S. Martins, José Francisco; H. N. Rangel, Paulo; dos Anjos Cutrim, Veridiano (Pesquisa Agropecuaria Brasileira, 2014)
Two experiments were conducted in the screenhouse in an attempt to identify sources of resistance to stem bug (Tibraca limbativentris Stal, 1860) in rice (Oryza sativa L.) Significant differences were observed among the cultivars and line, in relation to number and percentage of stems with dead heart, a symptom of insect attack during the vegetative phase. In general, the number of damaged stems was positively correlated with the tillering capacity of plants.